PENYULUHAN SANITASI KANDANG TERNAK SAPI PERAH - Rika, Rika; Reski Amaliah; Dewi Ramadani; Nursani, Nursani; Indriani, Indriani; Nur Lindah; Juanda, Juanda; Dinah Dwi Amaliah; M. Fachrin Agsa (Bajang Institute, 2024)
This service aims to provide counselling to the community or livestock groups in Baba Village, Cendana District, Enrekang Regency to maintain the sanitation of dairy cows in order to always maintain livestock comfort, livestock cleanliness, avoid bacterial contamination, avoid mastitis, and how to process a good waste processing process so that it can benefit the community in Enrekang Regency. This service location is a location where the majority of people own dairy farms. This service activity is expected by the community at this service location to be able to maintain good cage sanitation and can process livestock waste into useful, environmentally friendly products and increase selling points.